Impact of Paper Industry Effluents on Physico-Chemical, Microbiological and Enzyme Activities of Soil - Ramesh, B.; Mohan, P. Rama; Reddy, O.V.S. (Asian Journal of Biological and Life Sciences, 2013)
In a comparative study of various parameters between a paper industry effluent affected soil (test sample) and a control soil, it was formed that physico¬chemical changes like pH was higher (7.2) in affected test soil than the control (6.3) and electrical conductivity was more in the former (1.1) than the later (0.8). There were increased levels of water holding capacity, organic carbon, nitrogen, potassium and phosphorus in the test soil as compared to control which indicated the fertility of the former. There was two fold increase in the population of both bacteria and fungi; and also the enzyme levels (cellulase, xylanase, pectinase and invertase) were significantly higher in the test sample than the control, as these are indicators of microbial activity. These results indicate that paper industry effluents may increase the fertility of treated soil for plant growth.